Perancangan Motor Stepper Variable Reluctance Untuk Menggerakkan Saklar Pemindah - Yangly Pamma Refli; Budhi Anto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The availability of electrical energy is an important thing needed in everylife. To control if there is a power failure happened from the main supply (PLN) a device is needed, so that the reliability of the transmission system is maintained. This tool is known as the transfer switch the cam switch. When there is a disruption to the PLN electricity then the cam switch will automatically be moved to the generator supply, if the PLN electricity has improved then the cam switch is again moved to the PLN contact, and to move the cam switch is used an electric motor. In this research designed a stepper variable reluctance motor as a cam switch driver. Stepper variable reluctance motors are designed using magnet infolytica software with a combination of 6 stator poles and 4 rotor gears. The reluctance 6/4 stepper variable motor is expected to be able to drive the cam switch with a torque of 0.3 Nm and a 30-degree rotor step length. After being analyzed, it was obtained that the optimal dimension values with outer dimension of the stator 122 mm, inner diameter of the stator 72 mm, outer diameter of the rotor 71 mm and the machine length is 44.5 mm with 800 turns. The results of the analysis of the research obtained a machine torque value of 0.192 Nm. When the length of the machine is enlarged to 70 mm then the machine torque is 0.301 Nm, but the large flux density is 1.41 Tesla to 1.64 Tesla.Keywords : stepper variable reluctance motor, cam switch, software magnet infolytica